2018
DOI: 10.1002/aic.16326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the CaO sintering on the calcination rate of CaCO3 under atmospheres containing CO2

Abstract: For the calcination of CaCO3 under CO2‐containing atmospheres, a mathematical model taking into account the CO2‐catalyzed sintering of the CaO product layer is developed. In this model, a modified shrinking core model is coupled with a population balance‐based sintering model. By comparing model predictions with experimental data, it is found that CO2 strongly affects the overall calcination rate both at high temperature and CO2 partial pressure, since under these conditions CaO densification considerably redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The high enthalpy of the reaction and the high reaction temperature involves supplying a high amount of energy to the calciner, which can be satisfied by means of oxy-combustion to ensure an almost pure CO 2 stream at the calciner exit ready to be compressed and stored or reused. An important issue to be considered under these harsh calcination conditions is the enhanced CaO sintering, which negatively affects CaO conversion at the carbonator (Maya et al, 2018). To decrease the calcination temperature down to around 725 °C (Valverde and Medina, 2016), the CO 2 partial pressure should be reduced by introducing a certain amount of inert gas in the reactor such as steam or helium (Berger, 1927) that should be separable from CO 2 .…”
Section: Calcinermentioning
confidence: 99%
“…The high enthalpy of the reaction and the high reaction temperature involves supplying a high amount of energy to the calciner, which can be satisfied by means of oxy-combustion to ensure an almost pure CO 2 stream at the calciner exit ready to be compressed and stored or reused. An important issue to be considered under these harsh calcination conditions is the enhanced CaO sintering, which negatively affects CaO conversion at the carbonator (Maya et al, 2018). To decrease the calcination temperature down to around 725 °C (Valverde and Medina, 2016), the CO 2 partial pressure should be reduced by introducing a certain amount of inert gas in the reactor such as steam or helium (Berger, 1927) that should be separable from CO 2 .…”
Section: Calcinermentioning
confidence: 99%
“…properties (e.g. crystallite size, surface area, porosity) of the nascent CaO, which in turn determine its subsequent sorption properties for CO2 [148], [152]- [154]; this is elaborated in Section 2.5.1. On a plant level, the high endothermicity of the calcination reaction requires the co-combustion of a fuel, e.g.…”
Section: Cao-caco3 System (Calcite)mentioning
confidence: 99%
“…During the high-temperature calcination stage in the CaL, however, it is found that the calcium carbonate suffers to sinter due to its low Tammann temperature. As a result, a layer of the dense structure is formed on the solid adsorbent surface, which causes the difficulty of carbon dioxide diffusing in the solid adsorbent and then results in the degradation of adsorbent performance.…”
Section: Introductionmentioning
confidence: 99%